10.29406 Konstruksi Hukum dan Dualisme Regulasi Ijarah Muntahiyah Bi Al-Tamlik (IMBT) dalam PerbankanSyariah di Indonesia: Perspektif Pluralisme Hukum - Hanief Arkaan, Dimas Muhammad; Kurnia Nur Khodijah; Zikra Juninawan; Muhammad Dakhlan Gazali; Asnita, Dessy (Universitas Muhammadiyah Pontianak, 2026)
This study analyzes the legal construction and implementation of Ijarah Muntahiyah bi al-Tamlik (IMBT) within Indonesian Islamic banking from the perspective of legal pluralism and Islamic contract theory. Although IMBT is formally recognized as a Sharia-compliant lease-to-own financing instrument based on DSN-MUI Fatwa No. 27/2002, its practical implementation reveals a complex interaction between Sharia principles, state financial regulation, and institutional banking practices. This study employs a normative legal research method with statute, conceptual, and analytical approaches to examine the juridical structure of IMBT within Indonesia’s dual legal system. The findings indicate that IMBT operates as a composite legal structure combining ijarah and bay’, where the separation between contracts is often procedural rather than substantive. This condition generates a normative–institutional gap between classical Islamic contract theory and its modern financial implementation. Furthermore, the study reveals that regulatory dualism between DSN-MUI and the Financial Services Authority (OJK) contributes to interpretive fragmentation in IMBT execution. The novelty of this study lies in its reconceptualization of IMBT as a regulatory hybrid legal institution shaped by legal pluralism rather than a purely doctrinal Sharia contract. The study contributes to Islamic financial law literature by offering a critical framework for understanding the interaction between fiqh muamalah, regulatory governance, and banking standardization. The findings suggest the need for greater harmonization between Sharia governance and national financial regulation to ensure both doctrinal integrity and legal certainty in Islamic banking practice.